A conceptual perspective on natural disasters related information verification behaviors among youth on social media - Bolong, Jusang; Ahmad Ghazali, Akmar Hayati (Human Resource Management Academic Research Society, 2023)
Social media are known as powerful sharing tools; they can play an important role before, during, or after a natural disaster. Youth are closely attached to social media and are expected to be the leading receiver of natural disaster-related information. Understandably, they need to verify the information they received before considering using or sharing it; otherwise, fake news/information can be spread and chaos in the community. It is known that the existing models on information verification behavior have several areas for improvement, such as its study's scope (not focusing specifically on social media) and its methodological problem (sampling bias, sample size, the reliability of analysis performed, not having intervening variables). Due to this, improvements are required to suit the current setting. Hence, this review aims to understand several factors influencing youth's verification behavior on natural disaster-related information received from social media channels. The study explanation of several influential factors is expected to enhance understanding of the current pattern of verification behavior practiced by youth, and this enables interested parties to plan strategies in line with the youth's needs, abilities, and interests. Moreover, the study can serve as a basis for agencies such as NADMA to develop prevention strategies against fake information/news on natural disaster related information, especially one that is disseminated via social media.